Generative Unit Assessment: Authenticity in Mathematics Classroom Assessment Practices - P. Janelle McFeetors; Richelle Marynowski; Alexandra Candler (MDPI AG, 2021)
In our pursuit to broaden and deepen understandings of what it means to engage in an assessment activity, we explored the designing and implementing of a geometry performance task as an instantiation of authentic assessment to assess elementary school students' mathematics learning. Using participatory action research, we incorporated a performance task as an end-of-unit assessment with grade 4/5 students. We found that the authenticity within what we are calling a generative unit assessment, is understood as a process that is dynamic in contrast to conventional unit tests. We established an innovative assessment practice that emerged from the student and teacher data and is illustrated through four features applicable to any content area. Through collaborative discussions and the ensuing creation of a generative unit assessment, we found spaces to authentically understand ontological growth and continual learning through assessment.